2015
DOI: 10.17583/generos.2015.1502
|View full text |Cite
|
Sign up to set email alerts
|

Stereotypical Identities Discourse Analysis of Media Images of Women in Pakistan

Abstract: <p>Stereotypical portrayal of women through images and text in the media has been discussed and debated widely across the globe. The area remains relatively under published in the context of the third world especially Pakistan. To fill this gap this paper is an attempt to examine the role of the media in creating gender identities. Data for this study comes from selected English language newspaper namely “THE NEWS”. Discourse analysis of text and images - the most common way of producing and transmitting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 40 publications
1
12
0
1
Order By: Relevance
“…In spite of being an Islamic Republic state, Pakistani women are represented and generalized in the media as physically lovely and emotional. Ali and Batool (2015) criticized the oppressed and biased representation of women's identity in media. They claim that representation of Pakistani men and women in media delineates that women are essentially in charge of kid raising, home-production and they are needy and require men's assurance while men are in charge of pay and administration.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In spite of being an Islamic Republic state, Pakistani women are represented and generalized in the media as physically lovely and emotional. Ali and Batool (2015) criticized the oppressed and biased representation of women's identity in media. They claim that representation of Pakistani men and women in media delineates that women are essentially in charge of kid raising, home-production and they are needy and require men's assurance while men are in charge of pay and administration.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In Pakistan, however, research on gender has overwhelmingly focused on the construction and representation of womanhood and on women's issues in the context of religion, law, politics, development, economics, education, health (including reproductive rights), sexuality, and the media [52,56]. Recent studies on women and social media in the Pakistani context have also looked at online feminist resistance [57], the socio-economic empowerment of women via social media [73], the impact of social media on family dynamics [1], women's buying behaviour on social media [50] and the linguistic and semiotic construction of gender identities on Facebook [3]. Interestingly, this recent research emphasis on women has effectively rendered men invisible.…”
Section: Gender and Social Media Studiesmentioning
confidence: 99%
“…In Pakistan, where gender (especially femininities) has historically been a contested issue [1], the use of social media platforms such as Facebook can be a complex experience for both men and women [3] as it reflects the intricate interplay between individual autonomy and socio-cultural and religious pressures to conform. Pakistani men's and women's Facebook experiences are also deeply connected to and influenced by the daily practices and social interactions of their everyday lives, rendering the role of social media in bringing about social change even more complicated and powerful (ibid).…”
Section: Introductionmentioning
confidence: 99%
“…So, it can easily be observed that Pakistani TV serials are directly involved in rising male dominance. Ali & Batool (2015), Fogel (2012), Gürkan (2022), Giaccardi et al (2016Giaccardi et al ( -2017, Oppliger (2007), Srivastava & Roy (2011) and Torre (1990) argued that media had close-link with human and this media is found to reinforce the notion of conventional masculine and feminine. Media represents these gender views which are the main cause of negative traits separation (Levant & Richmond, 2008).…”
Section: Introductionmentioning
confidence: 99%